1981
DOI: 10.1152/jappl.1981.51.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ventilatory response to exercise in humans

Abstract: The dynamics of the ventilatory response to moderate exercise on a bicycle ergometer have been studied in humans. The work load was varied between 25 and 100 W as a pseudorandom binary sequence (PRBS) that enabled the impulse responses to be calculated by cross-correlation techniques. The response of all five subjects exhibited a bimodal response, i.e., a fast component that was followed after a delay by a slow component. The fast component accounted for a relatively small proportion of the total response. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Since the first component accounts for a relatively small portion of the total response, the over-all dynamics is mainly determined by the second component kinetics. A qualitatively similar dynamics has been observed in inspiratory ventilation volume (Vi) at transitions from a 25W basal exercise to a 100W impulse (BENNETT et al, 1981). WHIPP et al (1982) also observed similar responses in V02, and VE when a 10OW step work was given from loadless pedaling.…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…Since the first component accounts for a relatively small portion of the total response, the over-all dynamics is mainly determined by the second component kinetics. A qualitatively similar dynamics has been observed in inspiratory ventilation volume (Vi) at transitions from a 25W basal exercise to a 100W impulse (BENNETT et al, 1981). WHIPP et al (1982) also observed similar responses in V02, and VE when a 10OW step work was given from loadless pedaling.…”
Section: Methodssupporting
confidence: 69%
“…CASABURI et al (1977) and BAKKER et al (1980) compared the kinetics of heart rate, ventilation, and gas exchange parameters to define the interrelationship among variables during exercise. Other investigators used impulse forcings which differ from sinusoidal work in that a scale of frequencies can be given simultaneously (BAKKER et a!.,1980;BENNETT et a!., 1981;FUJIHARA et al, 1973a, b). In a linear system both the types of forcings would provide essentially the same results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach has been used to determine the dynamics of pulmonary gas exchange, namely, oxygen uptake (V O 2 ) and carbon dioxide excretion (V CO 2 ). TheV O 2 andV CO 2 responses to a constant moderate work load follow a pattern similar to that ofV E but with faster phase II kinetics of 30 to 35 s forV O 2 and 40 to 50 s forV CO 2 (37,63,66,343). Likė V E , theV O 2 andV O 2 time constants lengthen during heavy exercise and a steady state is never achieved.…”
Section: Characteristics Of the Exercise Hyperpneamentioning
confidence: 68%
“…4A), (37,63,66,343,347). The steady state is achieved within 3 min during light or moderate levels of exercise.…”
Section: Characteristics Of the Exercise Hyperpneamentioning
confidence: 99%